Lipid control and its associated factors among patients with type w diabetes mellitus attending government health clinics in Kuantan, Pahang - Said, Abdul Hadi; A Wahab, Syamimi Nadiah; Abd. Aziz, Karimah Hanim (Faculty of Medicine, UKM, 2023)
Studies have shown that type 2 diabetes mellitus (T2DM) and dyslipidaemia were strong predictors of the likelihood that an individual will develop cardiovascular (CV) disease. The main aim of this study was to ascertain the attainment of the primary target in lipid control specifically LDL-cholesterol (LDL-C) among patients with T2DM in primary care settings based on their individualised CV risk according to the latest local guideline. Materials and Methods: This multicentre cross-sectional study was conducted among patients with T2DM attending government health clinics in Kuantan using simple random sampling. The data were collected from the participants’ diabetes records. They were also asked to answer two validated questionnaires, International Physical Activity Questionnaire (IPAQ) and Malaysian Medication Adherence Assessment Tool (MyMAAT) to assess for the associated factors. Results: A total of 418 participants completed the study. Alarmingly, only 34 (8.1%) achieved the LDL-C target across all CV risk categories. Notably, those who were adherent to lipid-lowering medications and engaged in moderate physical activity were more likely to achieve the lipid target after multiple logistic regression analysis. Conclusion: The proportion of lipid control among participants was very low, emphasizing the urgent need for improvement. Promoting the importance of both physical activity and medication adherence is imperative to enhance these outcomes.